IITA donates 35,930 kilograms ‘Seeds of Renaissance’ to Nigeria_HE Olusegun Obasanjo's Speech - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
#IITA50 donates 35,930 kilograms ‘Seeds of Renaissance’ to Nigeria to address humanitarian crisis “Words cannot adequately convey the depth of our gratitude to IITA and to President Olusegun Obasanjo who is an Ambassador of IITA, for the choice of Borno State as beneficiary of a remarkable intervention. Seeds, particularly at this time, are life saving for us in Borno State. In a typical conflict situation, majority of farmers end up eating up their seeds because they can’t plant them." said The Governor of Borno State, Alhaji Kashim Shettima.